2020
DOI: 10.1186/s41983-020-00199-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-stroke depression: frequency, risk factors, and impact on quality of life among 103 stroke patients—hospital-based study

Abstract: Background Post-stroke depression (PSD) has worse functional outcomes and quality of life. Despite the extensive literature on this topic, there is no agreement on the frequency or risk factors for post-stroke depression. Objectives To establish the frequency and risk factors of post-stroke depression and its impact on quality of life. Patients and methods One hundred three stroke patients were recruited from the out-patient clinic of Qena University Hospital who satisfied the WHO definition for stroke, toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 51 publications
5
22
1
4
Order By: Relevance
“…Moderate QOL was predominant in post-stroke depressed patients, whereas severe SAQOL score is seen in PSA patients, consistent to the study conducted by Khedr et al [4] and Tang et al [18], respectively. SAQOL scores of baseline patients were compared with HAM D and HAM A to assess if the degree of decline in QOL patients with depression Sudden occurrence of neurological deficits might cause depression and anxiety in stroke patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Moderate QOL was predominant in post-stroke depressed patients, whereas severe SAQOL score is seen in PSA patients, consistent to the study conducted by Khedr et al [4] and Tang et al [18], respectively. SAQOL scores of baseline patients were compared with HAM D and HAM A to assess if the degree of decline in QOL patients with depression Sudden occurrence of neurological deficits might cause depression and anxiety in stroke patients.…”
Section: Discussionsupporting
confidence: 90%
“…Since the identification of PSD and PSA is a significant clinical problem, we evaluated the predictors that indicate patients at risk of developing PSD and PSA which include type of stroke, gender, QOL, etc. Early identification of PSD may improve the stroke outcomes and prevent psychiatric consequences Yihong Fang et al [4].…”
Section: Introductionmentioning
confidence: 99%
“…Smoking was a significant predictor of PSD in both our study and the study by Ayasrah et al [15]. It was also a significant predictor of PSD in other studies from our region and other regions [33,34]. It has been suggested that this correlation may be due to vitamin D deficiency in smokers in addition to the dysphoric effects of nicotine abstinence [33,34].…”
Section: Discussionsupporting
confidence: 75%
“…Based on the research carried out in this study, it can be concluded that health state and physical fitness do not affect the severity of the present clinical picture for hemiparesis caused by ischemic stroke, while patients who assess them better, show greater improvement during treatment. However, it is noted that the deterioration of socio-economic conditions, health, and physical fitness is a significant risk factor for depression [12,13,37].…”
Section: Discussionmentioning
confidence: 99%
“…Indicators of social isolation, poor material, and social situation, and positive medical history in terms of family burden of affective diseases can be treated as relatively wellsubstantiated. Since it is believed that lonesome patients living in poor housing conditions show a higher level of depression and more often stop receiving medical services and rehabilitation treatments [12,13].…”
Section: Introductionmentioning
confidence: 99%